Pitch Transcription of Solo Instrument Tones Using the Autocorrelation Method - Budhiono, Sofia Shieldy; Bayu Atmaja Darmawan, I Dewa Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 3 (2020): JELIKU Volume 8 No 3, February 2020DO - 10.24843/JLK.2020.v08.i03.p18, 2020)
Pitch transcription is basically identifying and copying pitch on an audio or music. In this case, the pitch of a solo instrument music is processed to find the composition of the music tones, the method used is autocorrelation. After processing, the system will produce pitch transcription results from the audio that has been processed. this research done digitalization of an old method of identifying pitches into an application that is able to transcribe pitches in an audio. This Pitch Transcription application was created using the Python programming language with Librosa library as a library for audio processing. The purpose of making this system is to facilitate the identification of pitch from a solo instrument music. This Application Feature itself besides being able to show the results of pitch transcription can also display the Onset Graph, Signal Graph play the results of the synthesis transcribed audio sounds. Testing in this study uses audio sourced from 4 single instruments, there are flute, piano, violin and acoustic guitar. The test results show that the implementation of the autocorrelation method in the solo instrument tone transcription application has an accuracy of 92.85%.